Common soil of smoking-associated and hormone-related cancers: estrogen deficiency - Zsuzsanna Suba (Frontiers Media S.A., 2011)
Accumulation of non-smoker, non-drinker elderly postmenopausal female patients among smokingassociated oral cancer cases raised the plausible idea: estrogen deficiency maybe a cancer risk factor. On the other hand, the extremely rare cases of young women with oral cancer regularly exhibited hormonal disorders, such as irregular menstrual cycles and infertility. Furthermore, in the history of middle-aged female, oral cancer cases a primary ovarian failure or complete hysterectomy was a conspicuously frequent finding suggestive of an estrogen deficient milieu. There were many striking contradictions concerning the associations of female sexual steroids and cancer risk as well. Until now, breast and endometrial cancers were regarded as typically estrogen-induced tumors, particularly in postmenopausal cases. However, unexplained beneficial anti-cancer effects of hormonereplacement therapy were reported against cancers at several sites, even tumors of the highly hormone-responsive organs. Re-evaluation of results of the experimental and epidemiological studies, which endeavored to justify the carcinogenic capacity of estrogen, exhibited many shortcomings and controversies. The new findings both on smoking associated and on hormone related cancers added up to the same conversion; not estrogen but rather its deficiency might provoke cancer initiation. Thorough review of the literary data justified that the exquisite regulatory capacity of estrogen and its surveillance on growth, development, differentiation, and metabolism are indispensable, whereas an estrogen-deficient milieu may induce a breakdown in gene-regulation. Recognition of the anticancer capacity of estrogen may provide new insights into the etiology of malignancies and leads to new strategies for cancer prevention and cure.